Efficacy and safety of tenofovir alafenamide versus tenofovir disoproxil fumarate given as fixed-dose combinations containing emtricitabine as backbones for treatment of HIV-1 infection in virologically suppressed adults: a randomised, double-blind, active-controlled phase 3 trial. Issue 4 (April 2016) - Gallant, Joel E; Daar, Eric S; Raffi, François; Brinson, Cynthia; Ruane, Peter; DeJesus, Edwin; Johnson, Margaret; Clumeck, Nathan; Osiyemi, Olayemi; Ward, Doug; Morales-Ramirez, Javier; Yan, Mingjin; et al.
Summary: Background: Emtricitabine with tenofovir disoproxil fumarate is a standard-of-care nucleoside reverse transcriptase inhibitor (NRTI) backbone. However, tenofovir disoproxil fumarate is associated with renal and bone toxic effects; the novel prodrug tenofovir alafenamide achieves 90% lower plasma tenofovir concentrations. We aimed to further assess safety and efficacy of fixed-dose combination emtricitabine with tenofovir alafenamide in patients switched from emtricitabine with tenofovir disoproxil fumarate. Methods: In this controlled, double-blind, multicentre phase 3 study, we recruited virologically suppressed (HIV RNA <50 copies per mL) patients with HIV aged 18 years and older receiving regimens containing fixed-dose combination emtricitabine with tenofovir disoproxil fumartate from 78 sites in North America and Europe. Patients were randomly assigned (1:1) to switch to fixed-dose 200 mg emtricitabine with 10 mg or 25 mg tenofovir alafenamide or to continue 200 mg emtricitabine with 200 mg or 300 mg tenofovir disoproxil fumarate, while remaining on the same third agent for 96 weeks. Randomisation was done by a computer-generated allocation sequence and was stratified by the third agent (boosted protease inhibitor vs other agent). Investigators, patients, and study staff giving treatment, assessing outcomes, and collecting data were masked to treatment group. The primary outcome was the proportion of patients with plasma HIV-1 RNA less than 50 copies per mL at week 48 as defined by the US Food and Drug Administration snapshot algorithm with a prespecified non-inferiority margin of 10%. The primary efficacy endpoint was analysed with the per-protocol analysis set, whereas the safety analysis included all randomly assigned patients who received at least one dose of study drug. This study is registered withClinicalTrials.gov, numberNCT02121795 . Findings: We recruited patients between May 6, 2011, and Sept 11, 2014; 780 were screened and 668 were randomly assigned to receive either tenofovir alafenamide (n=333) or tenofovir disoproxil fumarate (n=330). Through week 48, virological success (HIV-1 RNA <50 copies per mL) was maintained in 314 (94%) of patients in the tenofovir alafenamide group compared with 307 (93%) in the tenofovir disoproxil fumarate group (difference 1·3%, 95% CI −2·5 to 5·1), showing non-inferiority of tenofovir alafenamide to tenofovir disproxil fumarate. Seven patients in the tenofovir alafenamide (2%) and three (1%) in the tenofovir disoproxil fumarate group discontinued due to adverse events. There were no cases of proximal renal tubulopathy in either group. Interpretation: In patients switching from emtricitabine with tenofovir disoproxil fumarate to emtricitabine with tenofovir alafenamide, high rates of virological suppression were maintained. With its safety advantages, fixed-dose emtricitabine with tenofovir alafenamide has the potential to become an important NRTI backbone. Funding: Gilead Sciences.